Physical characteristics of a new cattle population “Bawri” in Chambal region of Madhya Pradesh - Jayakumar Sivalingam; SK Niranjan; Dinesh Kumar Yadav; SP Singh; PK Singh; Ajit Pratap Singh (Journal of Livestock Biodiversity, 2025)
Survey was conducted for exploration of new cattle germplasm in six districts of Chambal division of Madhya Pradesh. A unique cattle population “Bawri” was explored in Bijaipur Block of Sheopur district of Chambal subdivision. Further its distribution was also found to be in Morena district. Physical characteristics of Bawri cattle were studied for breed differentiation. Information about production, reproduction traits, migration pattern and other management system for Bawri/Garri cattle was also collected. The Bawri cattle are raised by Gurjars for milk under extensive system in ravine areas. The animals are medium in size; moderate to wild in temperament; coat is red-tan splashed with white colour; pink muzzle, eye lashes are blue, white to pink horns, lower side of belly is white in colour; hooves and tail switch; long and pointed horns, very large dewlap, small navel lap, adapted to low water intake and grazing in rough terrain of ravine area. Milk production is 2-4 Kg. Total population of Bawri cattle might be about 20-25 thousand. Local indigenous cattle are being preferred in this area due to adaptation of high temperature as well less intake of water. This indigenous cattle germplasm of Madhya Pradesh showed distinction in its physical characteristics and found to be different from the existing registered cattle breeds. The data generated in the study would be useful to characterize them in detail.